Supply Response of the Paddy Sector in West Malaysia - an Econometric Analysis - Villancio, Virgilio T. (1988)
Paddy production in West Malaysia showed impressive growth in 1967-73 with an annual growth rate of seven (7) percent. However, despite the increasing intervention of the government in the rice sector, paddy production in 1974-84 decreased with the highest decline in 1981-84 at an annual rate of 6.3 percent. This study is conducted to describe the pattern of supply response of paddy producers in West Malaysia for the period 1966-84 and to evaluate the impact of changes in the level of price support and subsidy, fertilizer subsidy and retail price of rice on total domestic paddy output with 1980-84 as the base period. The Nerlovian Adjustment Mode l (NAM ) is used to describe the paddy area and yield response to various formulation of the paddy, rubber and input prices, damage variable as a proxy for risk, dummy for unusual years, and lagged paddy area and yield. The estimated area planted and yield equations are used to estimate the paddy output and to evaluate the impact of price policy changes.